Iterative plug-in algorithms for SEMIFAR models - definition, convergence and asymptotic properties - Jan Beran; Yuanhua Feng (University of Konstanz, Center of Finance and Econometrics (CoFE), 2001)
In this paper data-driven algorithms for fitting SEMIFAR models (Beran, 1999) are proposed. The algorithms combine the data-driven estimation of the nonparamet- ric trend and maximum likelihood estimation of the parameters. Convergence and asymptotic properties of the proposed algorithms are investigated. A large simulation study illustrates the practical performance of the methods.
urn:nbn:de:bsz:352-opus-7430
Keywords: 330; semiparametric models; long-range dependence; fractional ARIMA; antipersistence; nonparametric regression; bandwidth selection; Nichtparametrisches Verfahren; Modellierung; Theorie; ARMA-Modell